2005
DOI: 10.2166/wqrj.2005.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oxygen Transfer Parameters from Four Testing Methods in Three Activated Sludge Processes

Abstract: In this investigation, the mass transfer of oxygen was determined using four different testing methods in three activated sludge processes, as per the guidelines established by the American Society of Civil Engineers (ASCE 1997). The testing methods applied included the steady-state oxygen uptake rate (OUR), the non-steady-state changing power level (CPL), the non-steady-state hydrogen peroxide addition (HPA) and the off-gas methods. The analysis indicated that steady-state OUR and off-gas methods resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For the use of in situ off-gas hoods DWA-M 209 (2007) estimated a measurement uncertainty of ± 5 to 10% for SOTR in activated sludge depending on tank shape and size. ASCE 18-18 (2018) referred to a comparison of several methods by Capela et al (2004) and Mahendraker et al (2005) and concluded that the examined methods estimated oxygen transfer parameters in activated sludge within 10 to 15% of each other depending on the examined method. Redmon et al (1983) originally reported a reproducibility of ± 10% for OTE with in situ offgas tests in activated sludge which primarily depended on changing conditions at a sampling point rather than accuracy of the analytical system.…”
Section: Estimation Of Measurement Uncertaintymentioning
confidence: 99%
“…For the use of in situ off-gas hoods DWA-M 209 (2007) estimated a measurement uncertainty of ± 5 to 10% for SOTR in activated sludge depending on tank shape and size. ASCE 18-18 (2018) referred to a comparison of several methods by Capela et al (2004) and Mahendraker et al (2005) and concluded that the examined methods estimated oxygen transfer parameters in activated sludge within 10 to 15% of each other depending on the examined method. Redmon et al (1983) originally reported a reproducibility of ± 10% for OTE with in situ offgas tests in activated sludge which primarily depended on changing conditions at a sampling point rather than accuracy of the analytical system.…”
Section: Estimation Of Measurement Uncertaintymentioning
confidence: 99%